Partisipasi politik buruh perempuan - Suryani Suryani; Ana Sabhana Azmy (Yinyang: Jurnal Studi Islam Gender dan Anak, 2020)
This study discusses the political participation of women workers in The Chemical, Energy and Mining Trade Unions of the All Indonesia Workers Union (SP KEP-SPSI). Using qualitative methods, this paper uses theories of women’s political participation, understanding sex and gender, and explaining socialist feminism as bases of analysis. This research tries to answer two issues namely how the involvement of women workers in the union in the SP KEP-SPSI and why the involvement of women in the union is important. The conclusion of this study is that the political participation of women workers in SP KEP-SPSI has not been actively involved enough in trade unions. Their membership is still very minimal with the indicator that there are only 4 female workers from 46 officials in the structure. However, SP KEP-SPSI has tried to facilitate the involvement of women workers with an indication of the inclusion of a clause on the involvement of women in the Statutes / Statutes of the Union. The involvement of women workers is important in unions, because it signifies a form of active political participation of citizens and is related to the struggle for the rights of women workers.